The ecology of breeding waterfowl at the Ouse Washes, England - Thomas, G J (Wildfowl, 1980)
Between 1968-1978 the mean annual density of breeding waterfowl at the Ouse Washes has been 63 prs/100 ha. Most species have shown general increases over the last 30 years and coincide with a slightly less rigorous drainage policy in the Spring. Breeding Gadwall Anas strepera and Tufted Duck Aythya fuligula have greatly increased due to the permanent pools provided in the last 10 years. Pre-breeding populations, especially of Mallard Anas platyrhynchos, Pintail Anas acuta and Coot Fulica atra were markedly higher when there were large amounts of spring floodwater. Dabbling ducks nested on higher ground, particularly the boundary and ditch banks, in the wetter springs. Their nest sites were on dry ground whilst those of Coot were surrounded by water: Moorhen Gallinula chloropus nests were intermediate. Gadwall, Tufted Duck and Pochard Aythya ferina nested within 10 m of water whilst other duck species nested between 10-60 m from water. The preferred duck nest sites were in tussocky growths, especially of Deschampsia caespitosa, whilst Coot preferred the non-tussocky Glyceria maxima. The height of vegetation at the nest was greater than around the nest for all species. Competition for nest space is probably not great in most years. Mallard and perhaps Gadwall and Tufted Duck preferred to nest in unused or lightly grazed fields whilst Shoveler Anas clypeata and perhaps Pintail preferred the more heavily grazed fields (> 90 cow days/acre). Coot and Moorhen showed no such preferences. Ditches and permanent pools held most of the waterfowl broods, whilst the temporary pools held most of the adults not involved in rearing young. The main duckling foods were probably the larger planktonic Crustacea and all the life stages of Chironomidae. The productivity of waterfowl appears low, with the mean brood sizes at fledging ranging from 2.5 for Mallard to 3.8 for Shoveler. At least for Mallard the greatest reduction in brood sizes occurred between quarter and half-grown young and coincided with low minimum grass temperatures in May. Also, suitable feeding areas are at a premium from May onwards as the water-bodies diminish. Mallard and Shoveler are the commonest ducks, whilst the remaining species nest at low densities and in some years are absent or rare. Consistently less water present in the spring in the future could see the disappearance of such species. In comparison to areas where water is a majority habitat the washes waterfowl populations are low. However, they are greater and richer in species than flood plains which have largely been drained for agriculture.